Equality adds quality: On upgrading higher education and research in the field of law - Baer Susanne (Anali Pravnog Fakulteta u Beogradu)
Much has been attempted, and many projects are still underway aimed at achieving equality in higher education and research. Today, the key argument to demand and support the integration of gender in academia is that equality is indeed about the quality on which academic work is supposed to be based. Although more or less national political, social and cultural contexts matter as much as academic environments, regarding higher education and research, the integration of gender into the field of law seems particularly interesting. Faculties of law enjoy a certain standing and status, are closely connected to power and politics, and are likely to feature resistance to equality efforts, both in the law itself and in the curriculum and research agenda. However, a multidimensional, intersectional gender analysis helps to reframe cases and doctrines, rulings and regulations far beyond the law that evidently affects women, which the headscarf controversies illustrate. In addition to gender competence, team diversity is a procedural device for success, and non-discrimination is a key requirement when diversity is meant to work. After all, such efforts - to expose bias and educate about gender in an academic field, to insist and integrate it continuously, and to not only demand but also do it - produce quality. Thus, gender equality is crucial for the achievement of the best possible results in higher education and research.